India-Sri Lanka maritime cooperation : opportunities and challenges - Vohra, Ravi; Srivatsan, V. (New Delhi : National Maritime Foundation, Anamaya Publishers, 2008)
"Contributed papers presented at a seminar organized by National Maritime Foundation"--
Keywords: India-Sri Lanka -- Diplomatic relations; Sea-power -- International cooperation